THE SIMULATION OF CO- AND CROSS-POLAR CHARACTERS OF RAINFALL DROPLETS AND CHAFF - Aldrian, Edvin (BPPT, 2002)
The error analyses and simulations of the co- and cross-polar characters of chaff andrainfall have been done. Error analyses include the ZDR distribution, numbers ofscaterers, the orientation and shape dependence, the system DC bias, the channel gainimbalance and the quantification errors. There is no effect of number of scatterers on the noise. The orientation and shape dependence study indicates wider frequency distribution of ZDR from chaff is because of the chaff's needle shape. The orientation of chaff contributes insignificantly to noises The noises has been reduced considerably after eliminating system DC bias and gaining more channel balance. Further possible source of error is the quantification error in data analyses. LDR is more useful than ZDR when both chaff and rain are present. The result suggests a possibility of using chaff?s LDR in tracing air movement.Analisa error dan simulasi sifat co- dan cross-polar dari chaff dan butir -butir hujan telahdilakukan. Analisa error termasuk penyebaran ZDR, jumlah chaff atau bidang pemantul(scatterers), orientasi dan bentuk dari chaff, factor kesalahan DC, keseimbangan keduakanal pada radar dan factor kesalahan kuantitatif unit. Tidak ada sumbangan kesalahandari jumlah scatterers pada noise. Penelitian orientasi dan bentuk menunjukkan lebarnya penyebaran ZDR pada chaff karena bentuknya. Orientasi dari chaff tidak menyumbang factor kesalahan yang berarti. Noise telah dapat dikurangi hingga minimal setelah menghilangkan factor kesalahan system DC dan menyeimbangkan kedua kanal. Faktor kesalahan lainnya yang mungkin adalah kesalahan kuantitatif unit pada analisis data. LDR lebih berguna dari ZDR ketika kedua duanya yaitu chaff dan butir hujan berada. Hasil tersebut menyarankan kegunaan chaff LDR untuk pemantauan pergerakan udara.